Implicit Theories of Mental Toughness: Relations With Cognitive, Motivational, and Behavioral Correlates - Gucciardi, Daniel; Jackson, B.; Hodge, K.; Anthony, D.; Brooke, Lauren (American Psychological Association, 2015)
People differ in their implicit theories about mental toughness, that is, whether they believe this quality is immutable (entity theorists) or changeable (incremental theorists). The aim of this study was to explore whether peoples’ implicit theories of mental toughness are related to cognitive, motivational, and behavioral variables considered as hallmarks of this personal quality. We conducted 3 studies with participants from different achievement contexts: 444 undergraduate students aged 17 to 26 years (M 19.25); 395 employees aged 25 to 79 years (M 48.78); and 230 adolescent athletes aged 11 to 17 years (M 14.98). Students completed a measure of implicit theories of mental toughness, fear of failure, and perceived stress. Employees completed a measure of implicit theories and were rated on performance and creativity by their supervisor. Athletes completed a measure of implicit theories of mental toughness, resilience, and thriving. Across all 3 samples, cluster analyses supported the existence of an incremental theory (high incremental theory, low entity theory) alongside an ambivalent group (moderate scores on both theories). These clusters differed on fear of failure, stress, performance, creativity, resilience, and thriving consistent with theoretical expectations. The current findings suggest that people’s implicit theories of mental toughness may have important implications for understanding cognitive, motivational, and behavioral correlates considered hallmarks of this psychological concept.